1993
DOI: 10.1016/0887-6177(93)90004-k
|View full text |Cite
|
Sign up to set email alerts
|

Clock drawing as an assessment tool for dementia

Abstract: Clock drawing has recently been shown to lie useful in differentiating Alzieimer's disease patients from normal controls. Our procedure for clock drawing differed from other published reports in that a copy condition was employed and patients were asked to set clock hands to read "ten after eleven". We found both clock drawing procedures to be correlated with tests related to executive and visuospatial functioning. In both conditions, nondemented controls performed significantly better than demented patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 0 publications
5
81
0
2
Order By: Relevance
“…By contrast, we found that CLOX 1 did not discriminate AD from VaD, although VaD patients performed worse in the CLOX 2 task. This finding can be explained by greater executive dysfunction and visuo-constructive impairment in VaD compared to AD, as already observed by other investigators 22,23 . Libon et al 23 showed that only AD patients' performance in CLOX 1 improved in relation to CLOX 2 when compared to VaD associated with SVaD.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…By contrast, we found that CLOX 1 did not discriminate AD from VaD, although VaD patients performed worse in the CLOX 2 task. This finding can be explained by greater executive dysfunction and visuo-constructive impairment in VaD compared to AD, as already observed by other investigators 22,23 . Libon et al 23 showed that only AD patients' performance in CLOX 1 improved in relation to CLOX 2 when compared to VaD associated with SVaD.…”
Section: Resultssupporting
confidence: 74%
“…This finding can be explained by greater executive dysfunction and visuo-constructive impairment in VaD compared to AD, as already observed by other investigators 22,23 . Libon et al 23 showed that only AD patients' performance in CLOX 1 improved in relation to CLOX 2 when compared to VaD associated with SVaD. These authors concluded that the copy condition may be sensitive to executive dysfunction and the impaired performance of AD patients in CLOX 1 might be explained by deficient semantic knowledge.…”
Section: Resultssupporting
confidence: 74%
“…Ten possible errors were scored on each trial. Cosentino et al, 2004;Libon et al, 1993Libon et al, , 1996 Language Boston Naming Test The dependent variable is the number of pictures correctly named.…”
Section: Executive Functions Phonemic Word List Generation (Fas)mentioning
confidence: 99%
“…This test appears to be diagnostically sensitive test for subcortical VaD. 23,24 Data from our laboratory show a high correlation between total clock-drawing errors and copy of the Rey Complex Figure 24,25 (−0.570 to −0.649, unpublished data).…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…Previous research has shown that total errors summed across the command and copy conditions are highly correlated with performance on tests of executive control and visuospatial ability. [21][22][23] Therefore, the dependent variable derived from this test was the total number of errors summed across the command and copy test conditions. This test appears to be diagnostically sensitive test for subcortical VaD.…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%